Pathways : Jack Reardigan - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1984)
In this episode host Cathy Boak interviews St. Bonaventure's alumnus and athlete Jack Reardigan. "A Memorial University Television Production, ©1984"